2017
DOI: 10.5935/abc.20170170
|View full text |Cite
|
Sign up to set email alerts
|

Permanent Pacing After Transcatheter Aortic Valve Implantation: Incidence, Predictors and Evolution of Left Ventricular Function

Abstract: BackgroundTranscatheter aortic valve implantation (TAVI) is a well-established procedure; however, atrioventricular block requiring permanent pacemaker implantation (PPI) is a common complication.ObjectivesTo determine the incidence, predictors and clinical outcomes of PPI after TAVI, focusing on how PPI affects left ventricular ejection fraction (LVEF) after TAVI.MethodsThe Brazilian Multicenter TAVI Registry included 819 patients submitted to TAVI due to severe aortic stenosis from 22 centers from January/20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 40 publications
0
20
0
6
Order By: Relevance
“…Table 1 shows the baseline characteristics of the included studies. The 36 studies included a total of 55,851 patients in the final analysis, from 2005 to 2018 [ 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 ]. The mean age of the patients was 81.9 years, with a mean STS score of 8.3.…”
Section: Resultsmentioning
confidence: 99%
“…Table 1 shows the baseline characteristics of the included studies. The 36 studies included a total of 55,851 patients in the final analysis, from 2005 to 2018 [ 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 ]. The mean age of the patients was 81.9 years, with a mean STS score of 8.3.…”
Section: Resultsmentioning
confidence: 99%
“…10) It has been well demonstrated that the incidence of PPI was higher in TAVI patients using Medtronic CoreValve than those using Edwards SAPIEN. [28][29][30] Gaede, et al 24) analyzed a cohort with 1025 patients who underwent TAVI procedure, which showed that the implantation of a CoreValve device is an independent predictor of PPI. A similar result was observed by Monteiro, et al 30) A possible reason why the patients who were treated with Medtronic CoreValve had a higher incidence of high-degree AV block than those treated with Edwards SAPIEN may be that the support frame of CoreValve prostheses could provide greater radial force, which continually exerts mechanical stress on the heart conduction system, than the stent of balloonexpandable SAPIEN devices.…”
Section: Discussionmentioning
confidence: 99%
“…[28][29][30] Gaede, et al 24) analyzed a cohort with 1025 patients who underwent TAVI procedure, which showed that the implantation of a CoreValve device is an independent predictor of PPI. A similar result was observed by Monteiro, et al 30) A possible reason why the patients who were treated with Medtronic CoreValve had a higher incidence of high-degree AV block than those treated with Edwards SAPIEN may be that the support frame of CoreValve prostheses could provide greater radial force, which continually exerts mechanical stress on the heart conduction system, than the stent of balloonexpandable SAPIEN devices. 24) Moreover, THVs with a long self-expandable stent such as CoreValve prosthesis will be deployed in a deeper position in the left ventricular outlet flow than that with short cylinder stent (Edwards SAPIEN or J-Valve) during TAVI procedure, which may increase the probability to compress cardiac conduction system.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Acute surgical trauma and perioperative ischemia following valve intervention can lead to cardiac conduction disturbances requiring pacemaker implantation in 3% to 6% of cases [1][2][3][4]. This incidence can increase to 20-27% after percutaneous/surgical aortic or tricuspid valve replacement [5][6][7][8]. Long term, valve surgery also remains associated with a higher risk of permanent pacemaker implantation with an incidence up to 25.9% at 10 years after triple valve replacement [9].…”
Section: Introductionmentioning
confidence: 99%